Digital operating model : the future of business - Sinha, Rajesh (Digital Strategist) (John Wiley & Sons, Inc., 2022)
"In this book, CEOs, CFOs, CIOs and Chief Digital Officers of organizations who have embarked on the journey of digital transformation but have not been able to fully realize the benefits will gain insights on aligning their existing investment with newer initiatives, as well as develop a proper roadmap for their digital future. Through the plans and actions of real-life examples of those who have attempted and achieved digital acceleration on their own or in client organizations, readers will learn the proper methods of creating multiple digital accelerators, how to culturally align to new agile ways of delivering rapid solutions, and become aware of new mantras of the API economy which can place digital strategy as the champion of today's successful business. Readers will learn how implementing a simple, but impactful digital platform strategy is the key to experiencing exponential business growth -- meeting your professional objectives while establishing innovative continuity and differentiation within your industry."--